Modeling of Road Performance Assessment Based on Pavement, Shoulder, and Drainage - Winurseto, Wahyu S.; Mulyono, Agus Taufik; Supama, Latif Budi (Institute for research and design in industry, 2023)
Measuring the value of road performance requires an emphasis on optimal performance demand. In Indonesia, pavement assessment is the sole basis for evaluating performance value. However, road performance is not solely determined by pavement performance, as the performance of road shoulder and drainage systems also influences it. This study aims to create a road performance evaluation model that is quantitative in nature, taking into account both pavement performance and the frequency and size of damages to road shoulders and drainage systems. To construct the model, this study employed a Structural Equation Model. According to the findings, the condition of the road shoulder and drainage systems had an impact on the road's performance, as measured by the International Roughness Index (IRI). The subsidence factor had the most significant impact on road shoulder performance (31.1%), then followed by waterlogging (29.4%), potholes (29.2%), and pavement edge height difference and road shoulder (5.3%), in addition to shoulder slope (5.0%). The road drainage performance, on the other hand, was influenced by the cross-sectional conditions of the road drainage channel (34.6%), structural drainage (31.1%), and drainage canal slope (29.2%). The study found that pavement, road shoulder, and drainage had a respective effect of 58.1%, 20.2%, and 21.7% on road performance.